Downregulation of Nuclear Protein H2B Induces Salicylic Acid Mediated Defense Against PVX Infection in Nicotiana benthamiana - Yang, Xue; Lu, Yuwen; Zhao, Xing; Jiang, Liangliang; Xu, Shengchun; Peng, Jiejun; Zheng, Hongying; Lin, Lin; Wu, Yuanhua; MacFarlane, Stuart; Chen, Jianping; Yan, Fei (Frontiers in Microbiology, 2019)
Histone H2B protein is not only structurally important for chromosomal DNA packaging but is also involved in regulation of gene expression, including the immune response of plants against pathogens. In this study, we show that potato virus X (PVX) infection resulted in reduced expression of H2B at both the mRNA and protein level in Nicotiana benthamiana. Tobacco rattle virus (TRV)-based virus-induced gene silencing (VIGS) was then used to down-regulate the expression of H2B in N. benthamiana and tests showed that the titre of TRV was similar in these plants to that in control treated plants. When these H2B-silenced plants were inoculated with PVX, the virus spread more slowly through the plant and there was a lower titre of PVX compared to non-silenced plants. Abnormal leaf development and stem necrosis were observed in the H2B-silenced plants, which were alleviated in H2B-silenced NahG transgenic plants suggesting the involvement of salicylic acid (SA) in the production of these symptoms. Indeed, quantitative reverse transcription (qRT)-PCR and liquid chromatography tandem mass spectroscopy (LC-MS) results showed that endogenous SA is increased in H2B-silenced N. benthamiana. Thus, downregulation of H2B induced accumulation of endogenous SA, which was correlated with stem necrosis and a decreased accumulation of PVX in N.benthamiana.